How to ADHD : an insider's guide to working with your brain (not against it) - McCabe, Jessica, 1982- (Rodale, 2024)
"The creator of the YouTube channel How to ADHD shares the insights and strategies that help her thrive in this accessible and shame-free guide to working with, understanding, and celebrating the ADHD brain"--